KLASIFIKASI KELAS PENARI WAYANG WONG MASA SULTAN HAMENGKU BUWANA V - Supriyanto Supriyanto (Institut Seni Indonesia Surakarta, 2009)
Names given to groups showing the levels of dancers are like social stratification of race in administrative law of foreign inhabitants in the territoryÂ of Sultan palace. The first level to which the best dancers belong is called Ringgit Gupermen. The second level is the group of moderate dancers AND is called Ringgit Encik. The beginners are grouped into a class called Ringgit Cina. The naming is probably influenced by the social stratification of foreign inhabitants living in the territory of the palace. Similarities in a class of dancers are determined by class consciousness. Sociologically, class consciousness is obtained automatically through skills and collective goals. So, class consciousness is related to the orientation of status symbol. This is not a problem for a nobleman because the consciousness is accepted automatically. It is not true for bureaucrats and priyayi (upper-class man). Their orientation of status symbol is attached to promotion. Key words : classification, class, dancer